Navigating air travel and cardiovascular concerns: Is the sky the limit?. Issue 9 (8th June 2017) - Hammadah, Muhammad; Kindya, Bryan R.; Allard‐Ratick, Marc P.; Jazbeh, Sammer; Eapen, Danny; Wilson Tang, W.H.; Sperling, Laurence
Abstract : As the population ages and our ability to care for patients with cardiac disease improves, an increasing number of passengers with cardiovascular conditions will be traveling long distances. Many have had cardiac symptoms, recent interventions, devices, or surgery. Air travel is safe for most individuals with stable cardiovascular disease. However, a thorough understanding of the physiologic changes during air travel is essential given the potential impact on cardiovascular health and the risk of complications in passengers with preexisting cardiac conditions. It is important for clinicians to be aware of the current recommendations and precautions that need to be taken before and during air travel for passengers with cardiovascular concerns.